The Role of Political Party Commitment in Improving Cadre Performance through HR Quality, Education, and Training - Ratnasari, Irma; Adi, Yusram; Amiruddin, Amiruddin (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine the effect of resource quality and training on political party commitment, the effect of resource quality, training and commitment on cadre performance, the effect of resource quality and training on political party commitment through cadre commitment. This study used a quantitative approach, by taking a sample of 128 cadres. Data collection techniques using questionnaire distribution, while data analysis techniques using path analysis and sobel test testing. The results of the research findings that resource quality has a positive and significant effect on commitment, training has a positive and significant effect, resource quality has a positive and significant effect on cadre performance, training has a positive and significant effect on cadre performance, commitment has a positive and significant effect on cadre performance. The results of the mediation test found that commitment can mediate the effect of resource quality and training on cadre performance at the Golkar party Dpw office in Southeast Sulawesi province.